Physical and electrochemical characterization of palm kernel shell biochar (PKSB) as supercapacitor - Wan Ab. Karim Ghani, Wan Azlina; Fernandez, Praveen Shawn; Halele, Mohamad Qayyum; Sobri, Shafreeza; Jasni, Jasronita (EDP Sciences, 2016)
A potential low cost and environmentally friendly supercapacitor has been prepared from Palm Kernel Shell Biochar (PKSB). In this study, physical and electrochemical properties of raw, activated and chemical treated (potassium hydroxide (KOH)) as supercapacitors such as high carbon content, high charge storage capacity and stable were evaluated. For physical analyses, the scanning electron microscopy (SEM) was used to study the surface morphology and surface area and porosity were measured using Brunaurer-Emmert-Teller (BET). The chemical treated PKSB shows the highest surface area values of 55.15 m2/g as compared to raw and activated samples with surface area are 0.17 m2/g and 19.32 m2/g, respectively. This is verified by in enhancement of capacitance achieved from 1.76 × 10−3 Fg-1 for the activated biochar and 1.87 × 10−6 Fg-1 for untreated PKSB showed by Raman spectroscopy. This enhancement reflected the charge storage capacity is attributed to the creation of broad distribution in pore size and a larger surface area. In addition, this phenomenon also supported by the electrochemical profiles through cyclic voltammogram (CV) measured by Potentiostat-Gavanostat (EIS). CV of the treated PKSB gave better square shape than the activated and raw biochar samples. These characterizations conclude that the raw palm kernel biochar need further treatment to become supercapacitor electrodes to replace activated carbon.